Drinking water consumption and association between actual and perceived risks of endocrine disrupting compounds - Sze, Yee Wee; Aris, Ahmad Zaharin; Md. Yusof, Fatimah; Praveena, Sarva Mangala; Harun, Rosta (Nature Portfolio, 2022)
Drinking water contains emerging contaminants, i.e., endocrine disrupting compounds (EDCs). However, the extent to which it is publicly viewed as a potential risk that requires attention (public awareness, political obligation, and regulatory efforts) is substantially underrated. Thus, this study investigated drinking water consumption patterns among consumers of different life stages, evaluated household practices using tap water as daily drinking water, and examined the actual risk as well as consumers’ perception of tap water quality for drinking with the potential EDCs contamination. Collectively, the present study is of great concern for regional database profiling and supporting human health risk assessment in regulating contamination and exposure of EDCs. It also provides an empirical and theoretical contribution to current public risk perception of EDCs in tap water, and promoted the formulation of risk communication and governance strategies for the development of risk behaviors in adopting public participation in the drinking water supply system monitoring and management framework.